2010
DOI: 10.1177/0884533610379606
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in Medicine

Abstract: Proper nutrition plays a key role in disease prevention and treatment. Many patients understand this link and look to physicians for guidance diet and physical activity. Actual physician practice, however, is often inadequate in addressing the nutrition aspects of diseases such as cancer, obesity, and diabetes. Physicians do not feel comfortable, confident, or adequately prepared to provide nutrition counseling, which may be related to suboptimal knowledge of basic nutrition science facts and understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(87 citation statements)
references
References 32 publications
(22 reference statements)
3
80
0
4
Order By: Relevance
“…A clear definition of competencies is important to steer curricular content – specifically, assessment – and students' approach to learning 90. A lack of agreement on the required competencies of students has also been identified in other areas of medical education – for example, global health 91 and nutritional medicine 92. It was not within the scope of the present review to determine why there is a lack of a consensus.…”
Section: Discussionmentioning
confidence: 94%
“…A clear definition of competencies is important to steer curricular content – specifically, assessment – and students' approach to learning 90. A lack of agreement on the required competencies of students has also been identified in other areas of medical education – for example, global health 91 and nutritional medicine 92. It was not within the scope of the present review to determine why there is a lack of a consensus.…”
Section: Discussionmentioning
confidence: 94%
“…In evaluating the status of nutrition education in the medical curricula, a number of studies in the USA [11][12][13] and other high-income countries [10,14,15] have found it to be inadequate. This has been corroborated by medical doctors reporting inadequate training in nutrition education during medical school, inadequate knowledge and skills in nutrition and feeling less efficacious in their ability to effectively provide nutrition care to patients [10,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…65 There is no debate that a healthy diet and eating behaviors are central to health and well-being and that health professionals should be cognizant of these facts 66,67 ; however, current evidence suggests that physicians do not feel adequately prepared to assume a prominent role in counseling their patients about good nutrition practices. 42 They indicate that they lack knowledge of nutrition science and the skills needed to apply nutrition interventions.…”
Section: Nutritionmentioning
confidence: 99%
“…The nutrition care process guides clinical practice for registered dietitians and registered dietitian nutritionists and is designed to provide a consistent and systematic approach for critical thinking and decision making to provide optimal patient care. 73 Adams and colleagues 66 previously proposed a detailed list of nutrition competencies for physi- cians and encouraged physicians, registered dietitians, and registered dietitian nutritionists to work collaboratively to implement nutrition care process domains. Essential domains include nutrition assessment, nutritional diagnosis, nutrition intervention, and nutrition monitoring and evaluation.…”
Section: Nutritionmentioning
confidence: 99%
See 1 more Smart Citation